2017
DOI: 10.14245/kjs.2017.14.4.126
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Junctional Kyphosis and Proximal Junctional Failure Following Adult Spinal Deformity Surgery

Abstract: The purpose of this review is the current understanding of proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) following adult spinal deformity (ASD) surgery. We carried out a systematic search of PubMed for literatures published up to September 2017 with “proximal junctional kyphosis,” “proximal junctional failure,” and “adult spinal deformity” as search terms. A total of 98 literatures were searched. The 37 articles were included in this review. PJK is multifactorial in origin and likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 51 publications
1
112
1
Order By: Relevance
“…Gum et al 14) reported the utilization of PSO procedure was increased by 3.2-fold within four years in the United States. In spite of the wide acceptance, the complication rate of PSO appears still higher than other spinal procedure 10,17,18,31) .…”
Section: Introductionmentioning
confidence: 96%
“…Gum et al 14) reported the utilization of PSO procedure was increased by 3.2-fold within four years in the United States. In spite of the wide acceptance, the complication rate of PSO appears still higher than other spinal procedure 10,17,18,31) .…”
Section: Introductionmentioning
confidence: 96%
“…Koda et al 12) suggested that dekyphosis should not be performed after posterior decompression because kyphosis correction may cause instrument failure. Hyun et al 6) also reported instrument failure following dekyphosis for treating adult spinal deformity. But, Zhang et al 27) confirmed by MR image that posterior migration and complete decompression of the spinal cord was possible through posterior approach with kyphosis correction.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to evaluate the natural progression of segmental kyphosis in the thoracic and thoracolumbar spine with age in old, normal asymptomatic men. PJK includes a wide range of symptoms, ranging from a symptomless deformity to severe pain that may require revision surgery [9,10,17]. However, it is fundamentally a radiographic pathologic that develops in the transitional region, usually between the UIV and two levels above the UIV.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal junctional kyphosis (PJK) develops after the surgery for adult spinal deformity, often causing clinical symptoms and needing revision surgery [4][5][6][7][8][9][10]. The selection of the level of the upper instrumented vertebra (UIV) is an important factor for avoiding the development of PJK in the surgery for adult spinal deformity [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%